Legal protection of employee wage rights in bankrupt companies: evidence from China - Jaelani, Abdul Kadir; Nuryanto, Ahmad Dwi; Fenitra, Rakotoarisoa Maminirina; Mujib, M. Misbahul; Luthviati, Resti Dian (Legality : Jurnal Ilmiah Hukum, 2023)
This study aims to identify the factors contributing to the legal protection of workers' wage rights in bankrupt companies in China, focusing on aspects that have not been grounded in social justice. This research is also to formulate and form a legal protection model for workers' wage rights in bankrupt companies based on social justice in Indonesia and China. This research is empirical. The research data is in the form of primary and secondary data (primary and secondary legal materials). The study results show that the factors that cause legal protection of workers' wage rights in bankrupt companies are not based on social justice and are the legal substance factor, namely the legal norms governing workers' wage rights and other rights. When a company goes bankrupt, there is non-uniformity in the priority hierarchy of creditors in the Bankruptcy Law, General Provisions on Tax Implementation Procedures, and Labor Laws. Another factor is the legal and structural factor, which only involves the trustee and supervisory judges in the settlement of bankrupt assets. The last factor is the legal culture, where participation in the payment of bankruptcy assets is minimal and the current economic system tends to be capitalist. Indonesia must take the Chinese government as an example; China places a premium on modifying labour standards to safeguard the rights and interests of workers in all circumstances and promote economic and social development.